A relação entre os estilos de socialização materna e as concepções de perdão em adolescentes. - Santos, Lydia Maria Sena e (2014)
The present study looked for to verify the relation among the adolescents' perception about the styles of maternal socialization and agreement with conceptions of the forgiveness. The styles of parental socialization are defined as patterns of performance characteristic, that the parents use in several situations of the daily. Those patterns are characterized by a group of techniques and forms of the parents' performance that include attitudes of acceptance until attitudes of control of unwanted behaviorsand imposition and imposing limits to the children. For Musitu and García (2001) the parental socialization is structured from two dimensions (Acceptance/Implication and Coercion/Imposition), that related they originate four models of parental styles: authoritative, authoritarian, indulgent and negligent. In that process, the mothers act in a suave way than the parents in the transmission of rules and moral values, being the forgiveness considered a moral value related to the compassion and the mercy. In the psychology of the moral, the forgiveness is considered as a value related to the justice and defined of point of view of the victim. In that sense, becomes important to study the relation between the styles of the mothers' performance and the conceptions of forgiveness adolescents. Participated in the study 186 adolescents, being 60 men and 126 women, with ages between 14 and 17 years old. As instruments were used: 1) a questionnaire biodemográfico with subjects about age, sex, série/ano; 2) a Scale about the conceptions of forgiveness; and 3) Parental Socialization Scale in Adolescence - ESPA29. The results showed that in your majority, the adolescents perceive the mothers as authoritative, being that parental style related to advanced conceptions of forgiveness. It was also found mothers sex difference in some conceptions of forgiveness. It was also found that mothers differ in socialization strategies between daughters and sons in some conceptions of forgiveness. Future studies should verify the reasons that the adolescents use to agree with the conceptions of forgiveness and if they are varied in detriment of parental style and the need of forgiveness in the interpersonal relationships.